A Comparative Study of National Educational Policies: A critical examination of Indian national educational policies (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study is intended to investigate the Indian education system, earlier National Education policies, its objectives, implementation, areas of failures and necessity for a new national policy on education in India and the challenges foreseen to new national educational policy. This paper is an attempt by the researcher to study different policies and their comparison related to the to school education system in post-independence period.